ANALISIS KOLABORASI BADAN METEOROLOGI KLIMATOLOGI DAN GEOFISIKA DENGAN KANWIL KEMENTERIAN AGAMA DALAM PENENTUAN HILAL PERSPEKTIF ILMU FALAK DI SULAWESI SELATAN - Sari, Erna; Syarif, Muh. Rasywan (HISABUNA: Jurnal Ilmu Falak, 2025)
Abstrak This examination talks about the Joint effort Investigation between the Meteorology, Climatology and Geophysics Organization and the Service of Religion in Deciding the Hilal Point of view of Falak Science in South Sulawesi. The fundamental issue is depicted in a few issue details, in particular: 1) What is the coordinated effort process between the Meteorology, Climatology and Geophysics Organization and Service of Religion in deciding the new moon?, 2) What are the elements that impact the cooperation between the Meteorology, Climatology and Geophysics Office and the Service of Religion in deciding the new moon? also, 3) What is the job of Falak Science innovation in supporting coordinated effort between the Meteorology, Climatology and Geophysics Organization and the Service of Religion? . The examination is named subjective , clear exploration with the exploration approaches utilized being: cosmic methodology, relative methodology, and juridical methodology. The data sources in this examination are essential data sources got from perceptions and meetings, while optional data sources are data acquired from books, diaries, propositions and logical compositions connected with the exploration object. The data assortment techniques utilized in this exploration are interview perception, documentation and writing study. Data the board and investigation: gathering subjective data and illustrative examination methods. The consequences of the exploration show that: 1) Deciding the new moon through a long interaction starts with holding a joint gathering to frame a rukyatul hilal group , gathering weather conditions conjecture data, setting up the devices utilized, deciding the area for doing rukyatul hilal exercises. 2) Can be isolated into two, in particular interior and outer elements. The inner variables alluded to are factors starting from the hilal or the moon, while outside factors are the area elements of the rukyat and perukyat. 3) advanced innovation in space science will give schooling to the general population in regards to deciding the new moon, that in a joint effort with the BMKG and the Service of Religion, it can add to the logical information on the's comprehension public might interpret the position and choices of the new moon. Gives understanding into stargazing and space science so this information can be valuable later on. The ramifications of this examination are: This exploration is about the cooperative investigation of the BMKG and the Service of Religion in deciding the hilal according to a cosmic point of view in the city of Makassar. It is trusted that the Middle for Meteorology, Climatology and Geophysics (BMKG) IV Makassar and the Territorial Office of the Service of Religion of South Sulawesi Area will focus closer and give data to the general population with respect to deciding the new moon, so the public will get genuine data. So issue focuses and answers for these issues can be gotten through interviews, direct perception, etc. In the event that there are numerous deficiencies, the creator requests information and upgrades.